2020
DOI: 10.1371/journal.pone.0236490
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and diastolic function in chronic spinal cord injury

Abstract: Individuals with spinal cord injury develop cardiovascular disease more than age-matched, non-injured cohorts. However, progression of systolic and diastolic dysfunction into cardiovascular disease after spinal cord injury is not well described. We sought to investigate the relationship between systolic and diastolic function in chronic spinal cord injury to describe how biological sex, level, severity, and duration of injury correlate with structural changes in the left ventricle. Individuals with chronic spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…For the estimated millions of people living with SCI globally (Singh et al, 2014;Kumar et al, 2018), altered autonomic cardiovascular regulation leads to chronic arterial blood pressure instability (Hubli et al, 2015;Katzelnick et al, 2019) with variation between hypotension that can be exacerbated by orthostasis (e.g., position changes) and severe hypertension triggered by autonomic dysreflexia (Blackmer, 1997;Teasell et al, 2000;Wecht et al, 2003;Dolinak and Balraj, 2007;Krassioukov et al, 2009;Wecht et al, 2013;Zhu et al, 2013). Studies on individuals with chronic SCI have identified blood pressure instability as one of the determinants of cardiovascular morbidity and mortality, including a 4-fold increased stroke risk in the SCI population (Su and Miao, 2005;Jegede et al, 2010;Rothwell et al, 2010;Wu et al, 2012;Muntner et al, 2015;Piatt et al, 2016;Stevens et al, 2016;Parati et al, 2018;Ditterline et al, 2020;Parati et al, 2020). Even in those without SCI, mounting evidence links blood pressure instability during orthostasis with poorer general physical and mental health (Wilkie et al, 1976;Wessely et al, 1990;Pilgrim et al, 1992;Rosengren et al, 1993;Barrett-Connor and Palinkas, 1994;Czajkowska et al, 2010;Vasudev et al, 2011;Regan et al, 2013;Briggs et al, 2016;Briggs et al, 2018;Shanbhag et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For the estimated millions of people living with SCI globally (Singh et al, 2014;Kumar et al, 2018), altered autonomic cardiovascular regulation leads to chronic arterial blood pressure instability (Hubli et al, 2015;Katzelnick et al, 2019) with variation between hypotension that can be exacerbated by orthostasis (e.g., position changes) and severe hypertension triggered by autonomic dysreflexia (Blackmer, 1997;Teasell et al, 2000;Wecht et al, 2003;Dolinak and Balraj, 2007;Krassioukov et al, 2009;Wecht et al, 2013;Zhu et al, 2013). Studies on individuals with chronic SCI have identified blood pressure instability as one of the determinants of cardiovascular morbidity and mortality, including a 4-fold increased stroke risk in the SCI population (Su and Miao, 2005;Jegede et al, 2010;Rothwell et al, 2010;Wu et al, 2012;Muntner et al, 2015;Piatt et al, 2016;Stevens et al, 2016;Parati et al, 2018;Ditterline et al, 2020;Parati et al, 2020). Even in those without SCI, mounting evidence links blood pressure instability during orthostasis with poorer general physical and mental health (Wilkie et al, 1976;Wessely et al, 1990;Pilgrim et al, 1992;Rosengren et al, 1993;Barrett-Connor and Palinkas, 1994;Czajkowska et al, 2010;Vasudev et al, 2011;Regan et al, 2013;Briggs et al, 2016;Briggs et al, 2018;Shanbhag et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of cardiac adaptation to increased afterload is therefore necessary, particularly as new research from our center has demonstrated that spinal cord epidural stimulation (scES) can normalize arterial blood pressure and mitigate orthostatic hypotension (Aslan et al, 2018;Harkema et al, 2018a;Legg Ditterline et al, 2020). Restoration of cardiovascular function at rest and during orthostatic stress would dramatically increase cardiac demand as individuals with spinal cord injury live with cardiac adaptation to persistent hypotension (Ditterline et al, 2020). Thus, we decided to investigate the effects of scES on cardiac structure and function.…”
Section: Introductionmentioning
confidence: 99%